Effects of different sampling intervals on apparent protein and energy digestibility of common feed ingredients by juvenile oscar fish (Astronotus ocellatus) - doi: 10.4025/actascianimsci.v34i2.10541 - Nascimento, Thiago Matias Torres do; Fabregat, Thiago El Hadi Perez; Rodrigues, Laurindo André; Sakomura, Nilva Kazue; Fernandes, João Batista Kochenborger (Acta Scientiarum. Animal Sciences, 2011)
This study evaluated the apparent protein and energy digestibility of common feed ingredients (soybean meal, fish meal, wheat meal and corn) by juvenile oscars using two different sampling intervals (30 min. and 12h). The 160 juvenile oscar fish tested (22.37 ± 3.06 g BW) were divided into four cylindrical plastic net cages, each one placed in a 1000 L feeding tank. The experiment was completely randomized in a 2 x 4 factorial design (2 feces collection intervals and 4 feed ingredients) with four replications. The statistical tests did not detect an interaction effect of sampling interval and type of ingredient on digestibility coefficients. Sampling interval did not affect protein and energy digestibility. The physical characteristics of juvenile oscar feces likely make them less susceptible to nutrient loss by leaching and can therefore be collected at longer intervals. Protein digestibility of the different ingredients was similar, showing that apparent digestibility of both animal and plant ingredients by juvenile oscars was efficient. Energy digestibility coefficients of fish meal and soybean meal were higher than those of wheat meal and corn. Carbohydrate-rich ingredients (wheat meal and corn) had the worst energy digestibility coefficients and are therefore not used efficiently by juvenile oscars.